PENGARUH PENGGUNAAN ABU TERBANG (FLY ASH ) TERHADAP KUAT TEKAN DAN PENYERAPAN AIR PADA MORTAR - Armin Naibaho; Takim Takim; Diana Ningrum (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2016)
Mortar or species is one of the building materials which serves to glue the bricks, brick, and stucco. During this time still using portland cement mortar and lime as the main connective materials are expensive. Therefore we need an alternative other connective materials that have cheaper prices and predicted can improve the compressive strength of mortar. Alternative fastening material used in this study is waste from coal combustion, ie fly ash (fly ash). This study uses a mixture of cement and sand composition of 1: 3 at a weight ratio of fly ash to cement amounted to 0%, 5%, 10%, 15%, 20%, 30%. Samples were tested compressive strength and water uptake is cube-shaped sample with a size of 5 cm x 5 cm x 5 cm. Based on the results of research conducted showed that the addition of fly ash was found to increase the compressive strength of mortar and act as filler so as to reduce water absorption, which in get the most optimum composition occurs in the percentage of 15% of the weight of the cement with the compressive strength at 28 days amounted to 420.00 Kg / cm² and water absorption of 1.67%